1981
DOI: 10.2307/3429220
|View full text |Cite
|
Sign up to set email alerts
|

Sources, Transport and Alterations of Metal Compounds: An Overview. I. Arsenic, Beryllium, Cadmium, Chromium, and Nickel

Abstract: An overview is presented of the current state of knowledge of the salient aspects of the sources, transport, and alterations of arsenic, beryllium, cadmium, chromium, and nickel. This information is considered vital for a better assessment of the scope of potential human hazard to these ubiquitous toxicants and their compounds. Stress is focused on both natural and industrial activities, particularly on the latter's projected trends. Increasing use patterns per se of most of these metals, as well as aspects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
3

Year Published

1983
1983
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 77 publications
0
19
0
3
Order By: Relevance
“…The lowest consumption is observed for the Peruvian Macchu Picchu Station due to its operation only in the austral summer (COMNAP, 2008). Therefore, the current consumption of fossil fuel by the research stations poses a potential risk of direct release of organic compounds and trace elements into the environment (Fishbein, 1981;Vouk and Piver, 1983;Bícego et al, 2009;Taniguchi et al, 2009).…”
mentioning
confidence: 99%
“…The lowest consumption is observed for the Peruvian Macchu Picchu Station due to its operation only in the austral summer (COMNAP, 2008). Therefore, the current consumption of fossil fuel by the research stations poses a potential risk of direct release of organic compounds and trace elements into the environment (Fishbein, 1981;Vouk and Piver, 1983;Bícego et al, 2009;Taniguchi et al, 2009).…”
mentioning
confidence: 99%
“…Furthermore, zinc is an important component of brass, bronze, die casting metal, other alloys, rubber, and paints. The environmental releases of zinc from sources of human origin far exceed the releases from natural sources [ 18 ] . The permissible concentrations of Zn in water and sediment/soil as per international standards are 5.0 mg/L and 300-600 mg/kg, respectively.…”
Section: Resultsmentioning
confidence: 98%
“…It is generally considered that Be is organically associated in most coals; however, Be may appear in quartz and clay minerals associated with coal (Swaine 1990). According to Fishbein (1981), "Be in the environment chiefly arises from coal combustion." Despite this finding, a careful study by Gladney and Owens (1976) showed that "less than 4% of the Be in the coal burned is being emitted to the atmosphere.…”
Section: Berylliummentioning
confidence: 99%